Clinical Evaluation of Poly(2-methoxyethylacrylate) in Primary Coronary Artery Bypass Grafting - Vang, See N. (J Extra Corpor Technol, 2005)
In an attempt to make cardiopulmonary bypass (CPB) less traumatic for patients undergoing cardiac surgery, extracorporeal circuits (ECC) have been modified to achieve this goal. Poly(2-methoxyethylacrylate) (PMEA, X-coating™) is a new polymer coating used in the ECC. PMEA studies have shown excellent biocompatibility with the components of blood. In this evaluation, PMEA-coated ECC were compared with control (CTR) circuits with emphasis on hematological parameters, perioperative homologous blood product usage, and clinical outcomes. Patients undergoing elective coronary artery bypass grafting were randomized to either a PMEA group (n = 30) or a CTR group (n = 30). Extracorporeal circuit components in the PMEA group were coated except for the cardioplegia delivery device and cannulas. Patients in the CTR group had just the arterial line filter coated. The following hematological parameters were measured: platelet count (PLT), white blood cell count (WBC), red blood cell count (RBC), and hematocrit (Hct). Blood product usage was observed along with clinical outcomes for the following parameters: ventilation time, mediastinal tube output, intensive care unit (ICU) and hospital lengths of stay. The preoperative patient profiles were comparable between the two groups. The PMEA group had marginally higher CPB times (134 ± 31.9 vs. 118 ± 33.7 minutes) and cross clamp times (83.9 ± 21.3 vs. 73.7 ± 21.6 minutes), however no significant differences were reached. Platelet count, RBC, and Hct levels were also comparable between groups with no significant differences. However, there was a significant difference in WBC between groups (p = 0.041). Less platelets were administered both intraoperatively and 48 hours postoperatively in the PMEA group. The authors evaluated PMEA-coating by measuring clinical outcomes, such as ventilation time, ICU and hospital lengths of stay, and homologous blood utilization. PMEA patients trended towards less homologous blood transfusions, which helped save an average of $83.41 per patient. Further clinical studies are needed to evaluate the benefits of this new polymer coating.